8x-7=9x-6

Simple and best practice solution for 8x-7=9x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-7=9x-6 equation:


Simplifying
8x + -7 = 9x + -6

Reorder the terms:
-7 + 8x = 9x + -6

Reorder the terms:
-7 + 8x = -6 + 9x

Solving
-7 + 8x = -6 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-7 + 8x + -9x = -6 + 9x + -9x

Combine like terms: 8x + -9x = -1x
-7 + -1x = -6 + 9x + -9x

Combine like terms: 9x + -9x = 0
-7 + -1x = -6 + 0
-7 + -1x = -6

Add '7' to each side of the equation.
-7 + 7 + -1x = -6 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = -6 + 7
-1x = -6 + 7

Combine like terms: -6 + 7 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| -9(z-1)=-8z-4 | | 15+16x= | | 28+3y=28 | | .91(8000-y)+.97y=7800 | | 15x+16=x | | n*2-23=0 | | -l-19l-1-23-2= | | -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 |

Equations solver categories